2007
DOI: 10.1111/j.1939-165x.2007.tb00438.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of lead poisoning on hematologic and biochemical values in trumpeter swans and Canada geese

Abstract: Lead toxicosis induced significant changes in the values of commonly measured hematologic parameters in waterfowl. These changes may be useful indicators of severe lead intoxication during routine laboratory assessment. Changes in clinical chemistry values, although statistically significant, were too inconsistent to serve as indicators of lead toxicosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
17
2
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 20 publications
2
17
2
1
Order By: Relevance
“…Hematology may show hemolytic anemia (mild to moderate) with Heinz bodies, poikilocytosis, polychromasia. The increased serum uric acid concentrations, LDH and total protein could be observed (O’Halloran et al 1988; Campbell and Ellis 2007; Katavolos et al 2007; Degernes 2008; O’Connell et al 2009). …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Hematology may show hemolytic anemia (mild to moderate) with Heinz bodies, poikilocytosis, polychromasia. The increased serum uric acid concentrations, LDH and total protein could be observed (O’Halloran et al 1988; Campbell and Ellis 2007; Katavolos et al 2007; Degernes 2008; O’Connell et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…The hematological values may be affected by time of day, moulting period, nutrition status, environmental conditions and applied treatment (e.g. steroids) (Shave and Howard 1976; Driver 1981; Whittow 1999; Artacho et al 2007a; Artacho et al 2007b; Katavolos et al 2007; Calabuig et al 2010; Milani et al 2012). …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…I read the recent publication on lead poisoning in which Katavolos et al 1 concluded: “Lead toxicosis induced significant changes in the values of commonly measured hematologic parameters in waterfowl. These changes may be useful indicators of severe lead intoxication during routine laboratory assessment.” I have some concerns about this report.…”
mentioning
confidence: 99%